The teaching approaches of Rungus gong music among Rungus community in Kudat, Sabah / Soferah Molupin Rongguan - Rongguan, Soferah Molupin (Faculty of Music, 2017)
Kampung Sumangkap is located in Kudat region, which is known as the tip of Borneo and "this is in the northeast part of Sabah. The community who lives in this village is mostly the Rungus people and they are well-known with gong-makers. They refer themselves as Momogun and among the traditional the music that they play uses the gong music to accompany various occasions such as engagement, marriage, birth and even death (Ongkili, J.P. 1969). The purpose of this research is to explore the teaching approaches used by the gong instructors in teaching gong music ensemble and the challenges faced in their teaching. This research was conducted through interviews and observations.